Novel Ni-Co-Mo-K Catalysts Supported on Multiwalled Carbon Nanotubes for Higher Alcohols Synthesis. (20th March 2013) - Surisetty, Venkateswara Rao; Kozinski, Janusz; Dalai, Ajay Kumar
Abstract : Alkali-promoted Ni-Co-Mo catalysts supported on multiwalled carbon nanotubes (MWCNTs) were prepared using 9 wt% K, 4.5 wt% Co, and 15 wt% Mo, whereas Ni content was varied from 0 to 6 wt%. The catalysts were extensively characterized and studied for higher alcohols synthesis from synthesis gas. Alkali-promoted trimetallic catalyst with 3 wt% Ni showed the highest total alcohols yield of 0.284 gm/(gm of cat./h), ethanol selectivity of 20%, and higher alcohols selectivity of 32% at 330°C and 9.0 MPa using gas hourly space velocity (GHSV) of 3.8 m 3 (STP)/kg of catalyst/h and H2 to CO molar ratio of 1.25.